 , 08.11.2019 01:31 danielanderson12

# If f(x) = 5x(3exponent) - 2 and g(x) = 2x+1 , find (f+g) (x) Answers: 2  ### Another question on Mathematics Mathematics, 21.06.2019 18:00
Each​ month, a shopkeeper spends 5x + 14 dollars on rent and electricity. if he spends 3x−5 dollars on​ rent, how much does he spend on​ electricity? for which​ value(s) of x is the amount the shopkeeper spends on electricity less than​ \$100? explain how you found the​ value(s).
Answers: 2 Mathematics, 21.06.2019 18:30
Which statement justifies why angle ebc measures 90?
Answers: 3 Mathematics, 21.06.2019 19:50
What is the solution to the equation below? 3/x-2+6=square root x-2 +8
Answers: 1 Mathematics, 21.06.2019 22:40
The value of x in this system of equations is 1. 3x + y = 9 y = –4x + 10 substitute the value of y in the first equation: combine like terms: apply the subtraction property of equality: apply the division property of equality: 3x + (–4x + 10) = 9 –x + 10 = 9 –x = –1 x = 1 what is the value of y?
Answers: 1
You know the right answer?
If f(x) = 5x(3exponent) - 2 and g(x) = 2x+1 , find (f+g) (x)...
Questions                    Questions on the website: 13321478